Nonlinearity compensation based robust tracking control of nonlinear nonminimum phase hypersonic flight vehicles. (December 2022) - Ren, Jinrui; Hang, Bin; Sang, Mouhua; Hong, Rui; Xu, Bin
Abstract: This paper introduces a nonlinearity compensation based robust tracking controller for hypersonic flight vehicles. The controller focuses on robust control design with respect to the nonminimum phase feature and system uncertainties for the control-oriented model. Firstly, following the principle of decomposing the complex control problem into two simpler problems, the original robust tracking problem for nonlinear nonminimum phase hypersonic flight vehicles is decomposed into a simpler robust tracking problem for a linear nonminimum phase system with disturbances and a stabilization problem for a nonlinear system without disturbances. After the problem decomposition, a proportional–integral tracking controller and a feedback linearization controller are designed for the linear system and the nonlinear system, respectively. Then, the addition of the two designed controllers gives the final controller. By compensating for the system nonlinearity using the secondary system and its controller, the proposed control method can satisfy the robust tracking control requirements for nonlinear nonminimum phase hypersonic flight vehicles. The simulation results show, compared with a feedback linearization control method and a composite neural learning control method, the proposed method has superior tracking accuracy and robustness against system uncertainties and external disturbances. Highlights: The challenging nonlinear robust tracking problem for HFVs is well solved. A novel same-order subsystem decomposition for HFVs is carried out. A type of two-degree-of-freedom control combined by PI control and FLC is proposed. Introducing nonlinearity compensation transforms the nonlinear NMP problem into a linear one. The proposed control method guarantees superior tracking accuracy and robustness.